(untitled) (Mongolian Journal of Agricultural Sciences, 2022)
The research was carried out in 2021 to determine the specific quality properties of local Mongolian breeds of cashmere goats. The research covered 122 herder households from 13 soums in 8 aimags. A total of 4,560 samples were collected from 1,522 goats representing the main factors determining cashmere quality: ecological habitat, various herd management practices, local breeds, age and sex of goats, and cashmere colour. Cashmere fibre diameter (FD), fibre curvature (FC), and coefficient of variation of fibre diameter (CVFD) were tested in 1,522 samples, and cashmere length was tested in 1,387 samples. The overall mean fibre diameter (MFD) was 16.1 μm, mean length (FL) was 44.9 mm, and fibre curvature (FC) was 61.9°/mm. Cashmere from one-year-old goats was significantly finer than cashmere from older goats (about 1.0 μm, P<0.05). Cashmere from does in the samples tested was significantly finer than cashmere from the bucks. Over the range in mean fibre diameter, from 13.5 to 19.0 µm, fibre curvature declined from 87.8 to 44.2°/mm. Of all cashmere samples, 40.6% belonged to super fine (≤15.5µm), 43.7% and 12.1% had a fibre diameter between 15.51-16.80 and 16.81-17.50 μm, respectively, and were suitable for knitwear. Only 3.6% of samples tested were between 17.51 to 19.00 μm and may only be suitable for weaving. The average CVFD values of cashmere of Mongolian breeds of cashmere goats was 22.5 ± 0.04%, with an individual range of 17.0-26.9%. This shows that it has lesser variation than Alashan white cashmere goats of Inner Mongolia Autonomous Region, China, where CVFD ranged from 27.09% to 41.39%. Compared to cashmere from China, Tajikistan, and Kyrgyzstan, with mean fibre curvature of 46, 46, and 58mm, respectively, the cashmere of local Mongolian breeds of goats would be considered curvier and longer, which makes stronger yarns. Short, higher crimped, softer cashmere may be preferred for woollen-spun yarns, but longer, lower crimped, softer cashmere may be preferred for woven yarn destined for knitwear. Fibre curvature of Mongolian cashmere goats declined an average of 6.1°/mm for a 1µm increase in MFD, which is similar to the 5.8°/mm observed in Chinese Liaoning goats, but less than the 13.6°/mm measured in controlled experiments with Australian goats. Significant differences were found between the cashmere of local Mongolian breeds of goats kept in open, natural rangelands and herded in a nomadic way in distinct ecological conditions of harsh continental climate compared to those breeds of goats kept in intensive farming. This shows the potential to offer distinct quality cashmere from local Mongolian breeds while maintaining proper management and selective breeding.